Utilizing Board Game as Media to Enhance Third Grade Students’ Understanding in Preposition of Place in an Elementary School in Malang - Novitasari, Elma Diana; Yuniar, Rendhi Fatrisna (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study investigates the effectiveness of board games as a learning medium to improve third-grade students' understanding of English prepositions of place. English, as an international language, plays a crucial role in global communication. Grammar instruction is introduced as early as elementary school; however, many students struggle with distinguishing grammatical components, particularly in prepositions of place. Traditional teaching methods often fail to support students in differentiating these concepts effectively. To address this issue, this study examines the use of board games as a learning medium to enhance students' understanding of grammar. Board games provide an interactive and engaging approach by incorporating game elements into the learning process. Using a one-group pretest – posttest classroom action research design with 27 participants at a public elementary school in Malang. The findings reveal a significant improvement in students' grammar mastery, as indicated by an increase in the average score from 70.2 (pre-test) to 87.1 (post-test) in the first cycle. Observations further demonstrate that board games enhance student engagement, foster a more enjoyable learning environment, and improve comprehension. These results suggest that incorporating board games into grammar instruction can be an effective strategy for young learners.